A generalized physical-based failure indicator parameter used in crystal plasticity model to predict fatigue life under low cycle fatigue and creep-fatigue loadings. (January 2023) - Zhou, Dewen; Wang, Xiaowei; Yang, Xinyu; Zhang, Tianyu; Jiang, Yong; Zhang, Xiancheng; Gong, Jianming; Tu, Shantung
Highlights: A dislocation motion-based failure indicator parameter (FIP) has been proposed. The physical meaning of the proposed FIP has been interpreted. Life predictions for low cycle fatigue and creep-fatigue loadings have been conducted. Abstract: A dislocation movement-based physical failure indicator parameter (FIP) was proposed and incorporated into crystal plasticity finite element to assess the damage for components subjected to low cycle fatigue (LCF) and creep-fatigue interaction (CFI) loadings. The concept of net slip was introduced through the distance of dislocation movement whose evolution was analyzed and compared with other FIPs. The creep damage can only be captured by the proposed physical FIP. Life prediction based on net slip was developed and validated for different materials under LCF and CFI loadings at different temperatures. Most of the predicted life falls in the ± 1.5 error bands.